Bio-priming with salt tolerant endophytes improved crop tolerance to salt stress via modulating photosystem II and antioxidant activities in a sub-optimal environment - Irshad, Khadija; Shaheed Siddiqui, Zamin; Chen, Jianjun; Rao, Yamna; Hamna Ansari, Hafiza; Wajid, Danish; Nida, Komal; Wei, Xiangying (Frontiers in Plant Science, 2023)
Abiotic stress is one of the major constraints which restrain plant growth and productivity by disrupting physiological processes and stifling defense mechanisms. Hence, the present work aimed to evaluate the sustainability of bio-priming salt tolerant endophytes for improving plant salt tolerance. Paecilomyces lilacinus KUCC-244 and Trichoderma hamatum Th-16 were obtained and cultured on PDA medium containing different concentrations of NaCl. The highest salt (500 mM) tolerant fungal colonies were selected and purified. Paecilomyces at 61.3 × 10-6 conidia/ml and Trichoderma at about 64.9 × 10-3 conidia/ml of colony forming unit (CFU) were used for priming wheat and mung bean seeds. Twenty- days-old primed and unprimed seedlings of wheat and mung bean were subjected to NaCl treatments at 100 and 200 mM. Results indicate that both endophytes sustain salt resistance in crops, however T. hamatum significantly increased the growth (141 to 209%) and chlorophyll content (81 to 189%), over unprimed control under extreme salinity. Moreover, the reduced levels (22 to 58%) of oxidative stress markers (H2O2 and MDA) corresponded with the increased antioxidant enzymes like superoxide dismutase (SOD) and catalase (CAT) activities (141 and 110%). Photochemical attributes like quantum yield (FV/FM) (14 to 32%) and performance index (PI) (73 to 94%) were also enhanced in bio-primed plants in comparison to control under stress. In addition, the energy loss (DIO/RC) was considerably less (31 to 46%), corresponding with lower damage at PS II level in primed plants. Also, the increase in I and P steps of OJIP curve in T. hamatum and P. lilacinus primed plants showed the availability of more active reaction centers (RC) at PS II under salt stress in comparison to unprimed control plants. Infrared thermographic images also showed that bio-primed plants were resistant to salt stress. Hence, it is concluded that the use of bio-priming with salt tolerant endophytes specifically T. hamatum can be an effective approach to mitigate the salt stress cosnequences and develop a potential salt resistance in crop plants.